2019
DOI: 10.1088/1755-1315/278/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Different species, life form, and complexity of dead coral head affect the species diversity and density of decapods

Abstract: High proportion of dead coral in coral reefs ecosystem are inhabited by a wide variety of associated organisms such as crustacean as a place to live. However, lack of study on the functional of dead corals in high diversity such Indonesian coral reefs. This study aimed to investigate the diversity and density of inhabitant decapod species from two different dead corals with different life form and complexity (Pocillopora verrucosa and Seriatopora histrix). A total of 235 individuals consisting of 7 families, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The presence of DCs in low coral reef ecosystems is thought to be a habitat that can support the diversity of another benthic biota. This is in line with the statement that dead coral reefs have the potential to become habitats for various decapods (Madduppa et al 2019) and even become one of the crab habitats (Ardiansah et al 2021). Another base substrate that has an almost equal percentage at each station is DCA, with the highest value at station 1, while stations 2 and 3 have almost the same percentage (34.3% and 34.0%, respectively).…”
Section: Resultssupporting
confidence: 87%
“…The presence of DCs in low coral reef ecosystems is thought to be a habitat that can support the diversity of another benthic biota. This is in line with the statement that dead coral reefs have the potential to become habitats for various decapods (Madduppa et al 2019) and even become one of the crab habitats (Ardiansah et al 2021). Another base substrate that has an almost equal percentage at each station is DCA, with the highest value at station 1, while stations 2 and 3 have almost the same percentage (34.3% and 34.0%, respectively).…”
Section: Resultssupporting
confidence: 87%
“…Xanthidae and Galatheidae were commonly found in shallow tidal, spread along rocky, cobble, and sandy substrate (Naderloo and Türkay, 2012). It was also found that Porcellanidae is the third highest abundant family after Xanthidae and Galathediae and has the highest number of specimens found in dead corals (Enochs and Manzello, 2012;Santos et al, 2012), especially on Pari Island (Madduppa et al, 2019). Furthermore,…”
Section: Biodiversity Of Crustacean Cryptic and Habitat Characteristicmentioning
confidence: 97%
“…Complex geomorphological characteristics and diverse life-form compositions can be used in biodiversity assessment. Certain life-forms are also known to affect the growth and development of organisms, particularly the abundance of fish (Madduppa et al, 2019), and some are highly sensitive to the coastal environment dynamics. Therefore, their spatial information can be the basis for monitoring, explaining the potential of and threats to coastal resources, and ultimately creating opportunities to build and grow the blue economy (Voyer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%